Comings and goings in the process of institutional diversification: The experience of Uruguayan universities in a comparative perspective - Pablo Landoni-Couture (Arizona State University, 2017)
The paper analyzes four higher education reform initiatives in Uruguay discussed between 2008 and 2014. Two of them, aimed at reforming the regulatory framework of higher education; the first one, proposed the creation of an accreditation agency, and the other modifying the rules under which private higher education operates. The other two had as their objective the establishment of new state universities. This study analyzes the contextual dynamics that influenced the formulation and decision-making of the initiatives, and attempts to explain the reasons why some proposals were successful and others not. The influence of international tendencies over these initiatives is analyzed regarding the technical and political dimensions in the design of the reform proposals and their discussion.